Writing scientific articles for undergraduate students: A need analysis - Khairun Nisa; Syahrul Ramadhan; Harris Effendi Thahar (International Journal of Evaluation and Research in Education (IJERE), 2023)
Excellent and appropriate teaching materials are based on the results of needs analysis. They significantly affect students’ ability to write scientific articles and increase their knowledge and understanding of scientific papers required by indexed and reputable journals. This article explores the target needs (i.e., necessities, lacks, and wants) for teaching materials based on accredited journal criteria for scientific article writing. The design used is a case study. The data were collected using a questionnaire about target needs based on the theory of Hutchinson and Waters, namely lacks, necessities, and wants, and a focus group interview. The results showed that students must learn about teaching materials to write scientific articles to improve their writing quality. Regarding the students’ lack of learning material for writing scientific articles, 85.53% indicated students’ lack of IMRAD or introduction, method, result and discussion, and conclusion format research articles. According to students’ perceptions, restating the research objective and approach and creating a research gap is the most difficult. Among 72 participants, 80% mentioned learning how to write based on the IMRAD format creating a research gap found to be the most critical skill they want to learn in the new course and then followed by summarizing and presenting data.